Aplicación de Fibrina Rica en Plaquetas en implantes dentales. - Choto Jimenez, Daysi Noemi (2024)
Platelet-rich fibrin (PRF) is a second-generation platelet concentrate that has proven to be highly effective in tissue healing and bone regeneration, particularly in the field of dental implantology. This study aims to analyze the role of PRF in dental implants through a bibliographic review of the last 10 years. The methodology consisted of a systematic literature review, selecting 30 articles from recognized scientific databases, following the PRISMA approach. Studies that examined the physiological properties of PRF, its advantages in implantology, and its proper clinical management were included. The results show that PRF improves tissue healing and bone regeneration due to the sustained release of growth factors such as VEGF and PDGF. Additionally, its use in implantology has been shown to reduce postoperative complications and accelerate osseointegration, enhancing implant stability. Proper handling of PRF, both in its solid and injectable forms, is crucial to maximize its clinical benefits. In conclusion, PRF is presented as a safe and effective tool in dental implantology, providing multiple benefits for soft and hard tissue healing. Its implementation in dental practice can significantly improve clinical outcomes and reduce recovery time for patients.